Meta-analysis of the effect of psychosocial skills training on the quality of life of people with schizophrenia - KARACA, SEMRA; ÖNGÜN, ESEN; ÜNSAL, GÜL (My University, 2022)
Purpose The purpose of this study was to synthesize the studies examining the effects of psychosocial skills training (PSST) on the quality of life of people with schizophrenia using a meta-analysis. Design and Methods Fifteen studies were included in the meta-analysis according to the inclusion and exclusion criteria. Findings PSST was found to have a moderate effect on the overall score of quality of life of individuals with schizophrenia, a moderate effect on the psychological dimension, and a low effect on the physical dimension. Practice implications It can be said that psychosocial skills training is an effective intervention that can be used to improve the quality of life of people with schizophrenia.
Keywords: Tıp; Sağlık Bilimleri; Hemşirelik; Medicine; Health Sciences; Nursing; HEMŞİRELİK; Klinik Tıp; Klinik Tıp (MED); Psikiyatri; NURSING; CLINICAL MEDICINE; Clinical Medicine (MED); PSYCHIATRY; Critical Care Nursing; Psychiatric Mental Health; Medical and Surgical Nursing; Pharmacology (nursing); Maternity and Midwifery; Oncology (nursing); Nursing (miscellaneous); Psychiatry and Mental Health; Advanced and Specialized Nursing; Nurse Assisting; LPN and LVN; General Nursing; Emergency Nursing; psychosocial skills training; quality of life; schizophrenia; SOCIAL COGNITION; REHABILITATION; OUTPATIENTS; OUTCOMES; FUNCTIONALITY; DEPRESSION; SYMPTOMS; PROGRAM; IMPACT; STIGMA; psychosocial skills training; quality of life; schizophrenia